Implementation of an ERAS Pathway in Colorectal Surgery - Cavallaro, Paul; Bordeianou, Liliana (Clinics in Colon and Rectal Surgery, 2019)
Enhanced Recovery after Surgery (ERAS) protocols have been demonstrated to improve hospital length of stay and outcomes in patients undergoing colorectal surgery. This article presents the specific components of an ERAS protocol implemented at the authors' institution. In particular, details of both surgical and anesthetic ERAS pathways are provided with explanation of all aspects of preoperative, perioperative, and postoperative care. Evidence supporting inclusion of various aspects within the ERAS protocol is briefly reviewed. The ERAS protocol described has significantly benefitted postoperative outcomes in colorectal patients and can be employed at other institutions wishing to develop an ERAS pathway for colorectal patients. A checklist is provided for clinicians to easily reference and facilitate implementation of a standardized protocol.
Keywords: enhanced recovery; colorectal; protocol